High-water-absorption dust-free cloth and preparation method thereof

Through the preparation method of modified polyamide fiber, combined with the addition of graphene, white carbon black and other materials, and through specific treatment steps, the shortcomings of dust-free cloth in water absorption and mechanical properties are solved, and the preparation of high-water absorption and dust-free cloth is achieved, with the advantages of simple process, low cost, environmental protection and high efficiency.

CN119824601APending Publication Date: 2025-04-15XIAMEN BAOSHILI DUSTLESS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046962.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing dust-free cloth has shortcomings in water absorption, wear resistance, antistatic properties and chemical stability, and it is difficult to meet the high requirements of modern industry. At the same time, the preparation process of modified polyamide fibers is complex, expensive, and environmental pollution problems need to be solved urgently.

Method used

Modified polyamide fibers are prepared by mixing polyamide and polyvinyl alcohol, and the water absorption and mechanical properties of the fibers are enhanced by adding materials such as graphene, white carbon black, succinic acid and 3-mercaptopropyltrimethoxysilane. Then, a highly absorbent dust-free cloth is prepared by weaving, water vapor heat treatment, hydrophilic soaking and UV curing treatment.

Benefits of technology

The preparation of high-water absorption dust-free cloth is realized, which improves the water absorption, wear resistance and durability of the fibers, and is simple in process, low in cost, environmentally friendly and efficient.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to high-water-absorption dust-free cloth and a preparation method thereof, and belongs to the technical field of dust-free cloth preparation. According to the invention, the polyamide fiber is used as a base material and is modified, and polyvinyl alcohol PVA is introduced and is mixed with polyamide, so that the water absorption of the fiber can be improved; the graphene has excellent water conductivity, and the white carbon black can increase the specific surface area and porosity of the fiber, so that absorption and retention of water are facilitated; succinic acid contains carboxyl and has certain hydrophilicity, so that the water absorption of the fiber can be further improved; the wettability and hydrophilicity of the surface of the fiber can be improved by introducing sulfydryl into the 3-mercaptopropyltrimethoxysilane, so that the fiber is more easily combined with water molecules, and the water absorption is improved; the base material obtained after weaving is subjected to water vapor heat treatment and hydrophilic agent soaking treatment, so that the hydrophilic performance of the cloth is enhanced; and the hydrophilic agent can be quickly fixed on the surface of the fiber through UV curing treatment, so that the hydrophilic agent is prevented from falling off or losing efficacy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dust-free cloth preparation, and relates to a highly water-absorbent dust-free cloth and a preparation method thereof. Background Art

[0002] Dust-free cloth is a cleaning material widely used in electronics, medical treatment, precision instruments and other fields. Its performance directly affects the cleanliness and production efficiency of the product. Traditional dust-free cloth is mainly made of natural fibers or synthetic fibers, but these materials have deficiencies in water absorption, wear resistance, antistatic properties, etc., and it is difficult to meet the high requirements of modern industry for dust-free cloth.

[0003] In order to improve the performance of dust-free cloth, researchers have begun to try to modify the fiber in recent years. As a new type of high-performance fiber, modified polyamide fiber has excellent water absorption, wear resistance, antistatic and chemical stability, making it an ideal material for preparing highly absorbent dust-free cloth. However, how to effectively prepare modified polyamide fiber and apply it to the preparation of dust-free cloth is still a technical problem.

[0004] At present, some preparation methods of modified polyamide fibers have been proposed, but these methods often have problems such as complex process, high cost, environmental pollution, etc. At the same time, in the preparation process of dust-free cloth, how to select a suitable hydrophilic agent and optimize the treatment process to improve the water absorption and cleaning performance of the dust-free cloth is also an urgent problem to be solved.

[0005] Therefore, developing a method for preparing modified polyamide fibers with simple process, low cost, environmental protection and high efficiency, and applying it to the preparation of highly absorbent dust-free cloths has important practical significance and application value. Summary of the invention

[0006] The object of the present invention is to provide a highly water-absorbent dust-free cloth and a preparation method thereof, which has the characteristics of high water absorption rate.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A highly absorbent dust-free cloth, the dust-free cloth is made of modified polyamide fiber,

[0009] The preparation method of the modified polyamide fiber is as follows:

[0010] S1.1: polyamide and polyvinyl alcohol are mixed in a mass ratio of (3-5):1, stirred in a mixing mixer at a speed of 300-350 r / min, and slowly heated to 90-100° C. while stirring to make the mixture molten, to obtain a mixture A;

[0011] S1.2: Graphene and white carbon black are mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 500 r / min for 1 to 2 h to obtain a mixed solid powder B;

[0012] S1.3: Add succinic acid to mixture A, the volume ratio of mixture A to succinic acid is 2:1, increase the speed of the mixer to 400 r / min, the stirring temperature is 30°C, and after stirring for 1 hour, add 5-7 wt% 3-mercaptopropyltrimethoxysilane, and then add 10 wt% mixed solid powder B and 2 wt% dispersant, and continue stirring for 2 hours to obtain mixture C;

[0013] S1.4: Put the mixture C into a twin-screw extruder to obtain fiber filaments after extrusion, and let it stand for 6 hours to obtain the modified polyamide fiber.

[0014] Furthermore, the rate of slow heating in S1.1 is 3°C / min.

[0015] Furthermore, the particle size of the mixed solid powder B in S1.2 is 800 mesh.

[0016] Furthermore, the dispersant in S1.3 is polyethylene glycol, and the number average molecular weight ranges from 2000 to 4000.

[0017] Furthermore, the parameters of the twin-screw extruder in S1.4 are a screw speed of 150 to 250 rpm and a temperature of 180 to 220°C.

[0018] A method for preparing a highly absorbent dust-free cloth, the specific steps of the preparation method are as follows:

[0019] S6.1: Weaving the modified polyamide fiber obtained in S1.4, and subjecting the obtained substrate to a steam heat treatment to obtain a substrate A;

[0020] S6.2: Soaking substrate A in a hydrophilic agent for 4 to 6 hours, and performing UV curing treatment after the soaking to obtain substrate B;

[0021] S6.3: The substrate B is placed in deionized water for rinsing for 10 to 15 minutes, and the highly absorbent dust-free cloth is obtained after drying.

[0022] Furthermore, the parameters of the steam heat treatment in S6.1 are as follows: the treatment time is 1 to 2 hours, the treatment temperature is 150 to 200° C., and the amount of steam introduced is 1.5 to 2 kg / h.

[0023] Furthermore, the preparation method of the hydrophilic agent in S6.2 is as follows: dissolve sodium silicate in deionized water to obtain a sodium silicate solution with a mass fraction of 30-40%, then mix the sodium silicate solution and ethylene glycol in a volume ratio of 2:1, and then add 3wt% of hexadecyltrimethylammonium bromide to obtain the hydrophilic agent.

[0024] Furthermore, the UV curing treatment parameters in S6.2 are ultraviolet wavelength of 355 to 365 nm and curing time of 5 to 10 seconds.

[0025] Furthermore, the drying parameter in S6.3 is drying at 70° C. for 12 hours.

[0026] The polyamide in the present invention was purchased from Nanjing Kangmanlin Chemical Industry Co., Ltd. with a purity of 98%; the polyvinyl alcohol in the present invention was purchased from Hefei Tianjian Chemical Co., Ltd. with a purity of 99%; the white carbon black in the present invention was purchased from Jinan Longcheng Silicone Co., Ltd. with a purity of 99.99%; the 3-mercaptopropyltrimethoxysilane in the present invention was purchased from Huangshan Kebery New Material Technology Co., Ltd. with a purity of 98%.

[0027] In the present invention, polyamide is used as a base material to provide the main mechanical properties and chemical stability of the fiber. Polyvinyl alcohol (PVA) is a polymer material with good water solubility and water absorption. After being mixed with polyamide, it can improve the water absorption of the fiber. Graphene has excellent water conductivity, and white carbon black can increase the specific surface area and porosity of the fiber, which is beneficial to the absorption and retention of water. In addition, as a nano material, graphene has excellent physical properties such as high strength and high modulus. Its uniform dispersion in the fiber can significantly improve the tensile strength, wear resistance and fatigue resistance of the fiber. White carbon black, as an inorganic filler, can increase the rigidity and hardness of the fiber, and at the same time improve the weather resistance and aging resistance of the fiber. Succinic acid contains a carboxyl group and has a certain hydrophilicity, which can further increase the water absorption of the fiber. 3-mercaptopropyltrimethoxysilane is used as a coupling agent to make the components more closely combined.

[0028] During the preparation process, polyamide and polyvinyl alcohol are mixed and heated to a molten state so that the two can be blended to a certain extent. The introduction of polyvinyl alcohol adds hydrophilic groups to the fiber, thereby improving the water absorption of the fiber.

[0029] Secondly, succinic acid was added to the mixture. As a hydrophilic substance, the carboxyl group of succinic acid can interact with the amide group in the polyamide molecule, further enhancing the hydrophilicity of the fiber. At the same time, the addition of succinic acid may also affect the arrangement and crystallinity of the polyamide molecules, making it easier for water molecules to penetrate into the fiber.

[0030] Furthermore, the addition of the mixture of graphene and white carbon black not only improves the mechanical properties of the fiber, but also may affect the water absorption performance of the fiber through its special microstructure. Both graphene and white carbon black have a large specific surface area and porosity, which help the fiber absorb and retain more water molecules.

[0031] Finally, 3-mercaptopropyltrimethoxysilane is used as a coupling agent to enhance the compatibility and bonding strength of the components in the fiber, ensuring that the fiber can maintain structural stability and integrity during water absorption. The addition of a dispersant helps to evenly distribute graphene and white carbon black in the fiber to avoid agglomeration.

[0032] The present invention adds 3-mercaptopropyltrimethoxysilane during the preparation process of the modified polyamide fiber. The mercapto functional group of 3-mercaptopropyltrimethoxysilane can react with the active group in the polyamide fiber to form a chemical bond, thereby enhancing the binding force inside the fiber; at the same time, it can also produce a good interaction with inorganic fillers such as graphene and white carbon black, thereby improving the dispersibility and binding force of these fillers in the fiber. The introduction of mercapto groups can improve the wettability and hydrophilicity of the fiber surface, making the fiber more easily combined with water molecules, thereby improving water absorption, but more importantly, 3-mercaptopropyltrimethoxysilane, as a silane coupling agent, can enhance the interaction between the fiber and water molecules, form a protective film, and improve the water resistance and wear resistance of the fiber, which is very important for highly absorbent dust-free cloths, because it needs to have good durability while maintaining high water absorption. By introducing 3-mercaptopropyltrimethoxysilane, the microstructure and properties of the fiber can also be adjusted, such as improving the tensile strength, elongation at break and elastic modulus of the fiber. The optimization of these properties helps to improve the overall quality and use effect of the highly absorbent dust-free cloth; the mercapto group of 3-mercaptopropyltrimethoxysilane can also participate in the cross-linking reaction and form a cross-linked network structure with other functional groups in the fiber. This cross-linking structure can further enhance the strength and stability of the fiber.

[0033] By subjecting the base material obtained after weaving to water vapor heat treatment, the fiber structure can be further stabilized, the overall performance of the fabric can be improved, and the base material can have better water absorption and durability. Soaking the base in a hydrophilic agent can enhance the hydrophilicity of the fabric, thereby increasing its water absorption speed and amount. The UV curing treatment can quickly fix the hydrophilic agent on the fiber surface to prevent it from falling off or becoming ineffective. Rinsing with deionized water can effectively remove residual impurities and hydrophilic agents to ensure the cleanliness of the dust-free cloth.

[0034] Hydrophilic agents can form a thin and uniform wetting film on the surface of fabrics, increase the wetting ability of the fabric surface, and make the fabric easier to wet. Adding hydrophilic agents in the production process of non-woven fabrics can give non-woven fabrics excellent hydrophilicity and make them have good liquid adsorption. Sodium silicate will form a network lattice structure in water and swell into a sponge-like viscous body with strong adsorption capacity. When the hydrophilic agent penetrates into the fiber and spreads on the fiber surface, sodium silicate will be adsorbed on the fiber surface and gradually form a thin film. Ethylene glycol and hexadecyltrimethylammonium bromide can be used as auxiliary ingredients to promote the formation and stability of the film. Ethylene glycol can increase the flexibility and adhesion of the film, while hexadecyltrimethylammonium bromide can reduce the surface tension of the film, making it smoother and more uniform.

[0035] Therefore, the sodium silicate, ethylene glycol, and hexadecyltrimethylammonium bromide in the hydrophilic agent of the present invention can penetrate into the fiber through the soaking process and form a thin film on the fiber surface. These components have hydrophilic groups, which can increase the surface tension of the fiber and reduce the contact angle between the non-woven fabric and water. When water molecules come into contact with the treated non-woven fabric, the hydrophilic groups can quickly attract and fix the water molecules, thereby achieving rapid water absorption; at the same time, the hexadecyltrimethylammonium bromide in the hydrophilic agent can also serve as a surfactant, which can accelerate the diffusion and adsorption of water on the fiber surface by changing the surface tension of the fiber, thereby further improving the hydrophilic properties of the non-woven fabric.

[0036] Beneficial effects of the present invention:

[0037] (1) In the present invention, polyamide fiber is used as the base material and modified to introduce polyvinyl alcohol (PVA). After mixing with polyamide, the water absorption of the fiber can be improved; graphene has excellent water conductivity, and white carbon black can increase the specific surface area and porosity of the fiber, which is beneficial to the absorption and retention of water; succinic acid contains carboxyl groups and has certain hydrophilicity, which can further increase the water absorption of the fiber; 3-mercaptopropyltrimethoxysilane is used as a coupling agent to make the components more closely combined. The introduction of mercapto groups can improve the wettability and hydrophilicity of the fiber surface, making the fiber easier to combine with water molecules, thereby improving the water absorption;

[0038] (2) The present invention further stabilizes the fiber structure and improves the overall performance of the fabric by subjecting the base material obtained after weaving to a steam heat treatment, so that the base material has better water absorption. Soaking the base material in a hydrophilic agent can enhance the hydrophilicity of the fabric, while UV curing can quickly fix the hydrophilic agent on the fiber surface to prevent it from falling off or becoming ineffective. Rinse with deionized water can effectively remove residual impurities and the hydrophilic agent, thereby ensuring the cleanliness of the dust-free cloth. DETAILED DESCRIPTION

[0039] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0040] Example 1

[0041] A highly absorbent dust-free cloth, the dust-free cloth is made of modified polyamide fiber,

[0042] The preparation method of the modified polyamide fiber is as follows:

[0043] S1.1: polyamide and polyvinyl alcohol are mixed in a mass ratio of 4:1, stirred in a mixing mixer at a speed of 350 r / min, and slowly heated to 90°C at a rate of 3°C / min while stirring to make the mixture in a molten state, to obtain a mixture A;

[0044] S1.2: Graphene and white carbon black were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 500 r / min for 2 h to obtain a mixed solid powder B with a particle size of 800 mesh;

[0045] S1.3: Add succinic acid to mixture A, the volume ratio of mixture A to succinic acid is 2:1, increase the speed of the mixer to 400 r / min, the stirring temperature is 30°C, and after stirring for 1 hour, add 6 wt% 3-mercaptopropyltrimethoxysilane, and then add 10 wt% mixed solid powder B and 2 wt% polyethylene glycol 2000, and continue stirring for 2 hours to obtain mixture C;

[0046] S1.4: Put the mixture C into a twin-screw extruder with the extruder parameters of a screw speed of 200 rpm and a temperature of 200° C. After extrusion, fiber filaments are obtained, which are allowed to stand for 6 hours to obtain the modified polyamide fiber.

[0047] A method for preparing a highly absorbent dust-free cloth, the specific steps of the preparation method are as follows:

[0048] S6.1: Weaving the modified polyamide fiber obtained in S1.4, and subjecting the obtained substrate to a steam heat treatment, wherein the parameters of the steam heat treatment are a treatment time of 2 h, a treatment temperature of 150° C., and a steam introduction rate of 2 kg / h, to obtain a substrate A;

[0049] S6.2: Substrate A is immersed in a hydrophilic agent for 6 hours, and then subjected to UV curing treatment after immersion. The UV curing treatment parameters are an ultraviolet wavelength of 355 nm and a curing time of 10 seconds, to obtain substrate B;

[0050] The preparation method of the hydrophilic agent is as follows: dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass fraction of 40%, then mixing the sodium silicate solution and ethylene glycol in a volume ratio of 2:1, and then adding 3wt% hexadecyltrimethylammonium bromide to obtain the hydrophilic agent;

[0051] S6.3: The substrate B is placed in deionized water for rinsing for 15 minutes, and dried at 70° C. for 12 hours to obtain the highly absorbent dust-free cloth.

[0052] Example 2

[0053] A highly absorbent dust-free cloth, the dust-free cloth is made of modified polyamide fiber,

[0054] The preparation method of the modified polyamide fiber is as follows:

[0055] S1.1: polyamide and polyvinyl alcohol are mixed in a mass ratio of 3:1, stirred at a speed of 300 r / min in a mixing mixer, and the temperature is slowly raised to 100°C at a rate of 3°C / min while stirring to make the mixture in a molten state, thereby obtaining a mixture A;

[0056] S1.2: Graphene and white carbon black were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 500 r / min for 1 h to obtain a mixed solid powder B with a particle size of 800 mesh;

[0057] S1.3: Add succinic acid to mixture A, the volume ratio of mixture A to succinic acid is 2:1, increase the speed of the mixer to 400 r / min, the stirring temperature is 30°C, and after stirring for 1 hour, add 5 wt% 3-mercaptopropyltrimethoxysilane, and then add 10 wt% mixed solid powder B and 2 wt% polyethylene glycol 4000, and continue stirring for 2 hours to obtain mixture C;

[0058] S1.4: Put the mixture C into a twin-screw extruder with the extruder parameters of a screw speed of 150 rpm and a temperature of 180° C. After extrusion, fiber filaments are obtained, and allowed to stand for 6 hours to obtain the modified polyamide fiber.

[0059] A method for preparing a highly absorbent dust-free cloth, the specific steps of the preparation method are as follows:

[0060] S6.1: Weaving the modified polyamide fiber obtained in S1.4, and subjecting the obtained substrate to a steam heat treatment, wherein the parameters of the steam heat treatment are a treatment time of 1 hour, a treatment temperature of 150° C., and a steam introduction rate of 1.5 kg / h, to obtain a substrate A;

[0061] S6.2: Substrate A is immersed in a hydrophilic agent for 4 hours, and then subjected to UV curing treatment after the immersion is completed. The UV curing treatment parameters are an ultraviolet wavelength of 365 nm and a curing time of 5 seconds, to obtain substrate B;

[0062] The preparation method of the hydrophilic agent is as follows: dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass fraction of 30%, then mixing the sodium silicate solution and ethylene glycol in a volume ratio of 2:1, and then adding 3wt% hexadecyltrimethylammonium bromide to obtain the hydrophilic agent;

[0063] S6.3: The substrate B is placed in deionized water for rinsing for 15 minutes, and dried at 70° C. for 12 hours to obtain the highly absorbent dust-free cloth.

[0064] Example 3

[0065] A highly absorbent dust-free cloth, the dust-free cloth is made of modified polyamide fiber,

[0066] The preparation method of the modified polyamide fiber is as follows:

[0067] S1.1: polyamide and polyvinyl alcohol are mixed in a mass ratio of 5:1, stirred in a mixing mixer at a speed of 350 r / min, and slowly heated to 100°C at a rate of 3°C / min while stirring to make the mixture in a molten state, to obtain a mixture A;

[0068] S1.2: Graphene and white carbon black were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 500 r / min for 2 h to obtain a mixed solid powder B with a particle size of 800 mesh;

[0069] S1.3: Add succinic acid to mixture A, the volume ratio of mixture A to succinic acid is 2:1, increase the speed of the mixer to 400 r / min, the stirring temperature is 30°C, and after stirring for 1 hour, add 7wt% 3-mercaptopropyltrimethoxysilane, and then add 10wt% mixed solid powder B and 2wt% polyethylene glycol 2000, and continue stirring for 2 hours to obtain mixture C;

[0070] S1.4: Put the mixture C into a twin-screw extruder with the extruder parameters of a screw speed of 250 rpm and a temperature of 220° C. After extrusion, fiber filaments are obtained, and the fiber filaments are allowed to stand for 6 hours to obtain the modified polyamide fiber.

[0071] A method for preparing a highly absorbent dust-free cloth, the specific steps of the preparation method are as follows:

[0072] S6.1: Weaving the modified polyamide fiber obtained in S1.4, and subjecting the obtained substrate to a steam heat treatment, wherein the parameters of the steam heat treatment are a treatment time of 2 h, a treatment temperature of 200° C., and a steam introduction rate of 2 kg / h, to obtain a substrate A;

[0073] S6.2: Substrate A is immersed in a hydrophilic agent for 6 hours, and then subjected to UV curing treatment after the immersion is completed. The UV curing treatment parameters are an ultraviolet wavelength of 365 nm and a curing time of 5 seconds, to obtain substrate B;

[0074] The preparation method of the hydrophilic agent is as follows: dissolving sodium silicate in deionized water to obtain a sodium silicate solution with a mass fraction of 40%, then mixing the sodium silicate solution and ethylene glycol in a volume ratio of 2:1, and then adding 3wt% hexadecyltrimethylammonium bromide to obtain the hydrophilic agent;

[0075] S6.3: The substrate B is placed in deionized water for rinsing for 10 minutes, and dried at 70° C. for 12 hours to obtain the highly absorbent dust-free cloth.

[0076] Comparative Example 1

[0077] In this comparative example, polyvinyl alcohol is not added in the preparation of the modified polyamide fiber, and the remaining steps are consistent with those of Example 1.

[0078] Comparative Example 2

[0079] In this comparative example, graphene and white carbon black are not added in the preparation of the modified polyamide fiber, and the remaining steps are consistent with those in Example 1.

[0080] Comparative Example 3

[0081] In this comparative example, no succinic acid was added during the preparation of the modified polyamide fiber, and the remaining steps were consistent with those of Example 1.

[0082] Comparative Example 4

[0083] In this comparative example, 3-mercaptopropyltrimethoxysilane was not added in the preparation of the modified polyamide fiber, and the remaining steps were consistent with those in Example 1.

[0084] Comparative Example 5

[0085] In this comparative example, no steam heat treatment is performed during the preparation of the dust-free cloth, and the remaining steps are consistent with those of Example 1.

[0086] Comparative Example 6

[0087] In this comparative example, no hydrophilic agent immersion treatment was performed during the preparation of the dust-free cloth, and the remaining steps were consistent with those of Example 1.

[0088] Comparative Example 7

[0089] In this comparative example, no UV curing treatment is performed during the preparation of the dust-free cloth, and the remaining steps are consistent with those of Example 1.

[0090] The water absorption of the embodiments and comparative examples was tested with reference to the standard GB / T 21655.1-2023. The sample size was 10 cm×10 cm. The experimental results are summarized in the following table.

[0091] Water absorption (%) Example 1 94.1 Example 2 93.8 Example 3 93.8 Comparative Example 1 83.3 Comparative Example 2 86.2 Comparative Example 3 85.1 Comparative Example 4 82.9 Comparative Example 5 89.8 Comparative Example 6 83.0 Comparative Example 7 90.6

[0092] Experimental data show that modification of polyamide fibers, as well as steam heat treatment, hydrophilic agent immersion treatment and UV curing treatment in the preparation process of dust-free cloths can effectively improve the water absorption of dust-free cloths.

[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A highly absorbent dust-free cloth, characterized in that: The dust-free cloth is made of modified polyamide fiber. The preparation method of the modified polyamide fiber is as follows: S1.1: polyamide and polyvinyl alcohol are mixed in a mass ratio of (3-5):1, stirred in a mixing mixer at a speed of 300-350 r / min, and slowly heated to 90-100° C. while stirring to make the mixture molten, to obtain a mixture A; S1.2: Graphene and white carbon black are mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 500 r / min for 1 to 2 h to obtain a mixed solid powder B; S1.3: Add succinic acid to mixture A, the volume ratio of mixture A to succinic acid is 2:1, increase the speed of the mixer to 400 r / min, the stirring temperature is 30°C, and after stirring for 1 hour, add 5-7 wt% 3-mercaptopropyltrimethoxysilane, and then add 10 wt% mixed solid powder B and 2 wt% dispersant, and continue stirring for 2 hours to obtain mixture C; S1.4: Put the mixture C into a twin-screw extruder to obtain fiber filaments after extrusion, and let it stand for 6 hours to obtain the modified polyamide fiber.

2. A highly absorbent dust-free cloth according to claim 1, characterized in that: The rate of slow heating in S1.1 is 3°C / min.

3. The highly absorbent dust-free cloth according to claim 1, characterized in that: The particle size of the mixed solid powder B in S1.2 is 800 mesh.

4. A highly absorbent dust-free cloth according to claim 1, characterized in that: The dispersant in S1.3 is polyethylene glycol, and the number average molecular weight ranges from 2000 to 4000.

5. A highly absorbent dust-free cloth according to claim 1, characterized in that: The parameters of the twin-screw extruder in S1.4 are a screw speed of 150 to 250 rpm and a temperature of 180 to 220°C.

6. A method for preparing a highly absorbent dust-free cloth, based on the highly absorbent dust-free cloth according to any one of claims 1 to 5, characterized in that: The specific steps of the preparation method are as follows: S6.1: Weaving the modified polyamide fiber obtained in S1.4, and subjecting the obtained substrate to a steam heat treatment to obtain a substrate A; S6.2: Soaking substrate A in a hydrophilic agent for 4 to 6 hours, and performing UV curing treatment after the soaking to obtain substrate B; S6.3: The substrate B is placed in deionized water for rinsing for 10 to 15 minutes, and the highly absorbent dust-free cloth is obtained after drying.

7. The method for preparing a highly absorbent dust-free cloth according to claim 6, characterized in that: The parameters of the steam heat treatment in S6.1 are as follows: a treatment time of 1 to 2 hours, a treatment temperature of 150 to 200° C., and a steam introduction rate of 1.5 to 2 kg / h.

8. The method for preparing a highly absorbent dust-free cloth according to claim 6, characterized in that: The preparation method of the hydrophilic agent in S6.2 is as follows: sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 30-40%, the sodium silicate solution and ethylene glycol are mixed in a volume ratio of 2:1, and 3wt% of hexadecyltrimethylammonium bromide is added to obtain the hydrophilic agent.

9. The method for preparing a highly absorbent dust-free cloth according to claim 6, characterized in that: The UV curing treatment parameters in S6.2 are ultraviolet wavelength of 355 to 365 nm and curing time of 5 to 10 seconds.

10. The method for preparing a highly absorbent dust-free cloth according to claim 6, characterized in that: The drying parameters in S6.3 are drying at 70° C. for 12 h.